A Novel Hybrid Meta-Heuristic Algorithm for Optimum Performance-Based Seismic Designs (PBSDs) of Steel Shear Walls (SSWs) - Behzad Eftekhar; omid rezayfar (Numerical Methods in Civil Engineering)
Steel Shear Walls (SSWs) exhibit suitable stiffness among various lateral force-resisting systems, and their application has been extended to tall buildings. In this research, the optimization of a High Performance-Based Seismic Design (HPBSD) of SSWs was introduced using a new optimization method. A hybrid algorithm was developed based on the Harmony Search (HS) algorithm, Multi-Design Variable Configuration (Multi-DVC) cascade optimization, and Upper-Bound Strategy (UBS). This new approach, termed MDVC-UHS, utilized cascade structural sizing optimization to manage numerous variables through a series of DVCs. The UBS was employed to reduce computational time, while the HS was used for global optimization. The MDVC-UHS algorithm was applied to optimize the dimensions of the steel shear wall in accordance with high performance-based seismic design principles. The research indicated that as the length of the SSW increased relative to its height, the more it was in the shear mode and the more usage it could have.